The effects of topical Arnica on performance, pain and muscle damage after intense eccentric exercise - Pumpa, K. L.; Fallon, K. E.; Bensoussan, E.; Papalia, S. (European Journal of Sport Science, 2014)
The aim of the study was to determine if topical Arnica is effective in reducing pain, indicators of inflammation and muscle damage, and in turn improve performance in well-trained males experiencing delayed onset muscle soreness (DOMS). Twenty well-trained males matched by maximal oxygen uptake (VO2 Max) completed a double-blind, randomised placebo-controlled trial. Topical Arnica was applied to the skin superficial to the quadriceps and gastrocnemius muscles immediately after a downhill running protocol designed to induce DOMS. Topical Arnica was reapplied every 4 waking hours for the duration of the study. Performance measures (peak torque, countermovement and squat jump), pain assessments (visual analogue scale (VAS) and muscle tenderness) and blood analysis (interleukin-1 beta, interleukin-6, tumour necrosis factor-alpha, C-reactive protein, myoglobin and creatine kinase) were assessed at seven time points over five days (pre-, post-, 4, 24, 48, 72 and 96 hours after the downhill run). Participants in the topical Arnica group reported less pain as assessed through muscle tenderness and VAS 72 hours post-exercise. The application of topical Arnica did not affect any performance assessments or markers of muscle damage or inflammation. Topical Arnica used immediately after intense eccentric exercise and for the following 96 hours did not have an effect on performance or blood markers. It did however demonstrate the possibility of providing pain relief three days post-eccentric exercise.